2021
DOI: 10.1002/bio.4174
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, microstructure characterization, and degradation performance of electrospun mats based on poly(3‐hydroxybutyrate‐co‐3 hydroxyvalerate)/polyethylene glycol blend for potential tissue engineering

Abstract: There have been strong demands for nanofibrous scaffolds fabricated by electrospinning for various fields due to their various advantages. Electrospun poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) fibre mats were prepared. The effects of processing variables as well as the inclusion of poly(ethylene glycol) (PEG) on the morphologies of generated fibres were investigated using Fourier-transform infrared spectroscopy and scanning electron microscopy. The average fibrous diameter was monitored in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They found that the cutaneous fibroblasts BJ-1 showed different adhesions and growth rates on the different types of PHBV fibers. The result indicated that PHBV mats with a low amount of PEG have a high potential for use in soft-tissue engineering, particularly in wound-healing applications [91]. In another publication, the authors designed an electrospun core-sheath mat made of polydioxanone (PDX) and PHBV.…”
Section: Phbv Composites For Tissue Engineering Applicationsmentioning
confidence: 99%
“…They found that the cutaneous fibroblasts BJ-1 showed different adhesions and growth rates on the different types of PHBV fibers. The result indicated that PHBV mats with a low amount of PEG have a high potential for use in soft-tissue engineering, particularly in wound-healing applications [91]. In another publication, the authors designed an electrospun core-sheath mat made of polydioxanone (PDX) and PHBV.…”
Section: Phbv Composites For Tissue Engineering Applicationsmentioning
confidence: 99%
“…In our knowledge, this is the first study to produce PHBV biopolymer though valorisation of collected cooked food waste. At the same time, electrospinning and electrospraying techniques appear promising prospects to address the shortage of bioplastics for medical and industrial applications by utilization of the PHBV biopolymer produced in this study (El-Newehy et al, 2021;Kaniuk & Stachewicz, 2021). and.…”
Section: Introductionmentioning
confidence: 97%